Implementation grounding of consumer-regulator to control electric loads in the power supply systems - Тихоненко, Станіслав Вікторович; Громадський, Юрій Степанович; Савицький, Сергій Михайлович; Гапон, Дмитро Анатолійович (Technology audit and production reserves, 2016)
This article discusses the use of combined heat power generation system by the automated electric heating units (customers, regulators) and the results of research. The main aim of this study is a feasibility study for the introduction of the automated control systems of electric load in electrical and heating systems of administrative buildings. The use of electrical accumulative heating systems, which are the consumers- regulators, enables alignment of the energy load curve in the power supply system for administrative buildings. In this article, we defined the technical and economic effect of the introduction of energy-efficient combined heat supply system with the accumulation of heat and three-band metering based on the automated transformer type unit for electric heating. Presented power supply system with built-in automated electric load control units can improve the energy efficiency of modes of distribution networks of power supply systems of administrative buildings. The evaluation of the overall effect of the alignment of the electric power system load curve gives an answer about the economic feasibility of the introduction of combined heating systems. The research results can be used in the design and development of electrical and heating systems of administrative buildings to control the selected load.